A circular compact ultra‐wideband antenna for 5G microwave applications - Swati Varun Yadav; Manish Varun Yadav; Tanweer Ali; Sounik Kiran Kumar Dash; Navya Thirumaleshwar Hegde; Vishnu G. Nair (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
This article introduces an innovative circular and compact ultra‐wideband (UWB) radiator designed specifically for 5G microwave applications. This antenna incorporates a “TU”-shaped ground plane on its reverse side, with strip lines feeding the circular element on the front side. Notably, the antenna exhibits impressive characteristics, including an outstanding impedance bandwidth of 107%, and an impressive return loss of -32 dB. Its operational frequency range spans from 2.4 GHz to 11 GHz, centered at 6.7 GHz. Extensive simulations were conducted using CST microwave studio software to validate its performance. The antenna’s physical dimensions are defined by a size of 0.12 λ × 0.08 λ × 0.012 λ relative to its wavelength. Furthermore, this antenna demonstrates exceptional stability in its polar patterns and maintains a high-efficiency level, achieving a substantial gain of 3.75 dBi with an efficiency rating of 84.5%. These remarkable attributes make this antenna suitable for a wide range of applications, including Wi-Fi, 5G, WLAN, and various other microwave communication scenarios.